Pharmacokinetic and Pharmacodynamic Interaction of Curcumin with Glimepiride in Normal and Diabetic Rats - Rani, Thatipamula Sandya; Sujatha, Samala; Veeresham, Ciddi (Pharmacognosy Communications)
Introduction: Herbal antidiabetic preparations are often used as an add-on therapy in diabetes and such herbal preparations often contain curcumin. Hence, in the present investigation the effects of curcumin on the pharmacokinetics and pharmacodynamics of glimepiride in normal as well as diabetic rats was studied. Methods: Pharmacokinetic study group I rats were administered with glimepiride (1 mg/kg; p.o.) on 8th day of the study. Group II rats were pretreated with curcumin (80 mg/kg; p.o.) for 7 days and on 8th day with glimepiride (1 mg/kg) followed by curcumin. Blood samples were collected at different time intervals and serum samples were analyzed using Highperformance liquid chromatography (HPLC). For the pharmacodynamic study, curcumin alone or in combination with glimepiride was administered to diabetic rats for 28 days and various biochemical parameters were determined. Total antioxidant status was determined by using the DPPH assay. Results: In normal and diabetic rats the combination of glimepiride with curcumin increased all the pharmacokinetic parameters including Cmax, AUC0 to n, AUCtotal, t1/2 and MRT. It also decreased the clearance, Vd markedly as compared to control group. The combination of glimepiride with curcumin provides significant protection against the diabetes induced alterations in the biochemical parameters. In addition, the combination of glimepiride with curcumin also improved the total antioxidant status. Conclusion: The results revealed that combination of glimepiride with curcumin led to the enhancement of bioavailability of glimepiride by inhibiting the CYP2C9 enzyme, which suggested that curcumin might be beneficial as an adjuvant to glimepiride in a proper dose, in diabetic patients.
Keywords: curcumin; CYP2C9; glimepiride; pharmacodynamics; pharmacokinetics